Gambaran Higiene Sanitasi Gerai Pangan Jajanan Keliling di Taman Kota Manggar Tahun 2022 - Indah Febriza; isti'anah Surury; Mizna Sabilla (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The development of food trends has formed new cultures such as culinary tourism, most of which are street food. Street food generally refers to ready-to-eat food prepared on the streets and sold by street vendors in public places. The purpose of this study is to determine the picture of sanitary hygiene of mobile snack food outlets in Manggar City Park in 2022. This type of research is descriptive research with a quantitative approach. The respondents in this study were all traveling snack food outlet vendors in Manggar City Park that existed during the study. Data collection in this study used observation and interview methods using a checklist sourced from the sanitation hygiene guidelines of food centers/canteens or the like that are safe and healthy by the Ministry of Health in 2021. The result of this study is that more than half (64%) of snack food outlets in Manggar City Park have a moderate risk of incompatibility and 35.3% with low categories. There are no food outlets with a high non-conformity risk category in Manggar City Park. The advice from this study is for traders to be able to apply sanitary hygiene according to the sanitary hygiene guidelines of food centers/canteens or the like that are safe and healthy. For the coordinator of the trader and the health office to be able to provide ready-to-eat food safety counseling to traders.